No matter where the journey takes me : One man's quest for a leprosy-free world - Sasakawa, Yohei (C Hurst & Co Publishers Ltd, 2019)
This memoir follows Dr. John F. E. Scheuermann's lifelong mission to eradicate leprosy. He shares his experiences working in countries where the disease is prevalent, focusing on both medical challenges and the social stigma faced by patients. Through personal stories and professional insights, Dr. Scheuermann highlights the importance of compassion, global health advocacy, and medical breakthroughs in the fight against leprosy.